2017
DOI: 10.1016/j.ajog.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 supplementation on pregnancy outcomes by smoking status

Abstract: BACKGROUND Smoking during pregnancy is associated with adverse maternal and neonatal outcomes such as preterm delivery, intrauterine growth restriction, stillbirth, and low birth weight. Since smoking causes oxidative stress, some have suggested using antioxidants to counteract the effects of oxidative stress. Smokers have lower serum levels of omega-3 fatty acids, an important antioxidant, and thus, investigating whether omega-3 supplementation in smokers reduces adverse maternal and neonatal outcomes represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Experiments in animal models have clearly shown that oxidative stress is responsible for maternal diabetes-induced NTDs 1, 7, 11, 5661 and congenital heart defects 62, 63 , and clinical research has demonstrated that oxidative stress is involved in various adverse pregnancy outcomes 64, 65 . For example, oxidative stress induced by tobacco smoke is associated with preterm delivery, intrauterine growth restriction, stillbirth, low birth weight, aberrant placental metabolism, syncytial knot formation, and multiple markers of oxidative damage 66, 67 . A case-control study showed that maternal oxidative stress may be an important contributor to preterm birth, regardless of subtype and timing of exposure during pregnancy 68 .…”
Section: Commentmentioning
confidence: 99%
“…Experiments in animal models have clearly shown that oxidative stress is responsible for maternal diabetes-induced NTDs 1, 7, 11, 5661 and congenital heart defects 62, 63 , and clinical research has demonstrated that oxidative stress is involved in various adverse pregnancy outcomes 64, 65 . For example, oxidative stress induced by tobacco smoke is associated with preterm delivery, intrauterine growth restriction, stillbirth, low birth weight, aberrant placental metabolism, syncytial knot formation, and multiple markers of oxidative damage 66, 67 . A case-control study showed that maternal oxidative stress may be an important contributor to preterm birth, regardless of subtype and timing of exposure during pregnancy 68 .…”
Section: Commentmentioning
confidence: 99%
“…There were no notable differences between groups. However, the trial was not designed with this specific effect in mind, hence lacking the power to detect it confidently [ 65 ]. Nevertheless, this secondary analysis may become an example for future study designs because smoking affects pregnant women in non-obvious ways.…”
Section: Studies Concerning Association Between Lcpufa and Preeclamentioning
confidence: 99%
“…In this case, omega-3 supplementation was associated with lower risk of spontaneous preterm birth in smokers (RR=0.56; 95% CI; 0.36-0.87) than in nonsmokers (RR=1.04; 95% CI; 0.84-1.29). In addition, low birth weight was less often diagnosed in babies born from smokers subjected to omega-3 supplementation (RR=0.57, 95% CI 0.36-0.90) than in babies born from nonsmokers (RR=0.93; 95% CI; 0.71-1.24) [29].…”
Section: Discussionmentioning
confidence: 96%